The Effect of Application of Teacher Centered Learning, Cooperative Learning and E-Learning Methods on Students' Understanding of Accounting Learning: Pengaruh Penerapan Metode Teacher Centered Learning, Cooperative Learning Dan E-Learning Terhadap Pemahaman Mahasiswa Pada Pembelajaran Akuntansi - Diana Septy Mega Altino; Sigit Hermawan (Academia Open, 2020)
This research aims to know the influence of the application of a method of teacher centered learning cooperative learning and E-learning againt understanding a student on the learning accounting. The variables examined in this study is teacher centered learning, cooperative learning and understanding a student. This study used a quantitative approach with the collection of data technique using the questionnaire. Sample is all the accounting students semester 6 and 8 had embarked on a course called accounting as many as 200 students .The method of analysis data used in this research was multiple linear regression. Based on the research and discussion done, can be summed up and can be concluded The application of teacher centered learning cooperative learning and E-learning to depend on the understanding a student on the learning accounting partial and simultaneous